2010
DOI: 10.1021/ja101877a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Selective Halogenation by SyrB2: A Computational Study

Abstract: The mechanism of the chlorination reaction of SyrB2, a representative α-ketoglutarate dependent halogenase, was studied with computational methods. First, a macromolecular model of the Michaelis complex was constructed using molecular docking procedures. Based on this structure, a smaller model comprising the first- and some of the second-shell residues of iron and a model substrate was constructed and used in DFT investigations on the reaction mechanism. Computed relative energies and Mössbauer isomer shifts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
161
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(177 citation statements)
references
References 61 publications
13
161
2
Order By: Relevance
“…It was shown that positioning of the substrate and H-bond interactions of the incipient OH lead to the selection of a C-H abstraction reaction channel that brings the newly formed substrate radical into the proximity of the chloro ligand. [44,232] Recent experiments fit well into the overall picture. [233] At the same time, it seems that intrinsic properties of the metal complex may also play a role here, as it was found that the synthetic [Fe IV (O)(TPA)Cl] + complex has an appreciable preference toward rebound to the ligand in the cis position with respect to the amine nitrogen of TPA, as a result of the different bond strengths.…”
Section: Chemoselectivitymentioning
confidence: 57%
“…It was shown that positioning of the substrate and H-bond interactions of the incipient OH lead to the selection of a C-H abstraction reaction channel that brings the newly formed substrate radical into the proximity of the chloro ligand. [44,232] Recent experiments fit well into the overall picture. [233] At the same time, it seems that intrinsic properties of the metal complex may also play a role here, as it was found that the synthetic [Fe IV (O)(TPA)Cl] + complex has an appreciable preference toward rebound to the ligand in the cis position with respect to the amine nitrogen of TPA, as a result of the different bond strengths.…”
Section: Chemoselectivitymentioning
confidence: 57%
“…We briefly considered an alternate form of the reactive complex, which has been shown to form through a rearrangement involving a high energy transition state (33), with an equatorial Fe(IV)ϭO and axial chlorine to identify whether reactivity differences could be a result of changes in the position of the Fe(IV)ϭO. By studying the reactivity of L-Thr with this alternate complex, we found hydrogen abstraction to be less favorable and hydroxylation to be preferred.…”
Section: Resultsmentioning
confidence: 99%
“…The established accordance between DFTϩU theory and experimental biochemistry motivates further study into identifying substrate-dependent and position-dependent reactivity in larger models of both SyrB2 and the PPant tether. Importantly, DFTϩU preserves the favorable scaling of standard DFT approaches used in previous SyrB2 studies (31,32) while providing even more accurate descriptions of transition-metal chemistry without any of the model size limitations of more expensive approaches (33). These first principle DFTϩU simulations of SyrB2 with PPant tethers will elucidate tether active site interactions and identify the role of tethered substrate delivery in determining the type of product formed in this class of alkane-functionalizing enzymes.…”
mentioning
confidence: 94%
“…Finally three snapshots were selected from the MD trajectory, at 300, 400, and 500 ps. The reaction energy profiles were calculated for all snapshots and all possible spin states using B3LYP, B3LYP* BP86, and M06 (Becke, 1993;Borowski, Noack, Rado n, Zych, & Siegbahn, 2010;Lee, Yang, & Parr, 1988;Reiher, Salomon, & Artur Hess, 2001) but in all cases gave the spin state ordering of quintet < triplet < singlet.…”
Section: Novel Modifications In Enzyme Structures May Produce Reactivmentioning
confidence: 99%